2018
DOI: 10.3390/su10020452
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Entrepreneurship and Business Sustainability

Abstract: Sustainability is becoming increasingly important for society, and the creation of business ventures is one area where sustainability is critical. We examined the factors affecting actions that are designed to foster business sustainability. These factors are related to the environment, behavior, human relations, and business activity. Based on questionnaire responses from experts, the Analytic Hierarchy Process (AHP) method was used to rank sustainable business criteria according to their importance for entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 58 publications
3
76
0
3
Order By: Relevance
“…Furthermore, the environmental (green movement) connotation dominates categorization to the detriment of social and economic considerations. The dynamics of the human memory formation support recent proposals (Corner, ) for fresh, uncompromised terminology to articulate the challenges of sustainability management.Proposition Enhanced sustainability management requires greater psychological salience in personal goal‐setting with emphasis on prosocial outcomes (see, for example, Tur‐Porcar, Roig‐Tierno, & Llorca Mestre, ).Proposition The success of sustainability management will be a function of the social status accorded to sustainable behaviour (see, for example, De Nardo, Brooks, Klinsky, & Wilson, ).Proposition Sustainability management is constrained by established associations existing in memory linked to the traditional connotations of sustainability. Is it time to think in terms of a new concept?…”
Section: Neuroscientific Insights Relevant To Sustainability Managementsupporting
confidence: 54%
“…Furthermore, the environmental (green movement) connotation dominates categorization to the detriment of social and economic considerations. The dynamics of the human memory formation support recent proposals (Corner, ) for fresh, uncompromised terminology to articulate the challenges of sustainability management.Proposition Enhanced sustainability management requires greater psychological salience in personal goal‐setting with emphasis on prosocial outcomes (see, for example, Tur‐Porcar, Roig‐Tierno, & Llorca Mestre, ).Proposition The success of sustainability management will be a function of the social status accorded to sustainable behaviour (see, for example, De Nardo, Brooks, Klinsky, & Wilson, ).Proposition Sustainability management is constrained by established associations existing in memory linked to the traditional connotations of sustainability. Is it time to think in terms of a new concept?…”
Section: Neuroscientific Insights Relevant To Sustainability Managementsupporting
confidence: 54%
“…Some of the most distinct factors in driving sustainability were behavioral factors or habits that seem to be the norm within a business. Tur‐Porcar, Roig‐Tierno, and Mestre () demonstrated that behavioral factors such as motivation, lifestyle, and metacognition scored higher compared with human relations and business factors. They focused on the hierarchical design of the key factors that influence entrepreneurial sustainability.…”
Section: Drivers and Barriers To Smes' Sustainabilitymentioning
confidence: 99%
“…First, business growth and the sustainability of start-ups are generally introduced to have a high correlation with entrepreneurship [34,38,49,50]. Zahra [51] discovered that there is a significant relationship related to entrepreneurship measured in terms of innovativeness, proactiveness, and risk taking, to the sustained growth of a company.…”
Section: Researchers Competencesmentioning
confidence: 99%
“…This definition considers that the business sustainability of start-ups can be fulfilled by continuously achieving financial sustainability through generation of economic profits, while also obtaining the employment sustainability, possibility of providing more services, and competencies in order to maintain growth engines. This study measured this with five items: such as 'sustained growth', 'sustained employment', 'sustained sales increase', 'sustained investment', and 'sustained competitiveness', as based on the studies by Lim [83] and Tur-Porcar et al [50].…”
Section: Variables and Analytical Approachmentioning
confidence: 99%
See 1 more Smart Citation